A cross-cultural, qualitative research study: comparison of The Coca-Cola Company television advertisements in China and South Africa - Egling, Minke (The IIE, 2016)
The objective of this research project was to investigate how The Coca-Cola Company advertisements are adapted according to cultural variability in South Africa and China. Five television advertisements, acting as social artifacts were analysed, advertising the products Coca-Cola, Sprite and Fanta. Three analysis models were applied to these advertisements. Firstly, the culture and context framework of Norlyk was employed to analyse how culture influences the form and content of the advertisements. Secondly, to analyse the extent of advertising standardisation, Harris and Attour’s model of analysis was employed. The scoring results based on Harris and Attour’s model of analysis placed the advertisements on the continuum, depending on the extent of advertising standardisation or adaptation of the advertisement. Finally, Hofstede’s model of analysis was employed to account for the possible cultural differences between South Africa and China in terms of collectivism and individualism on a national level. This was done to determine how it affects the execution as well as the linguistic elements and to account for the cultural differences in consumers’ buying behavior. The results of the findings pointed in the direction of advertising standardisation for an iconic product such as Coca-Cola while concentrating on both collectivistic and individualistic appeals, but adaptation for other Coca-Cola products such as Sprite and Fanta. The elements less likely to be standardised in Coca-Cola’s secondary products proved to be the product names as well as the product settings of the advertisements, since English and Chinese language structures and landscapes are very different. The results of the findings indicated that varying buying behavior in China and South Africa influences the extent of advertising standardisation, which points in the direction of advertising adaptation.
Keywords: Cross-cultural advertising